Path-Following Algorithms for Posynomial Geometric Programming Problems - Yang, Hsu-Hao (Journal of the Chinese Institute of Industrial Engineers, 2000)
Geometric programming (GP) is a class of optimization problems with a nonlinear objective function subject to a set of nonlinear constraints. The problems considered in this paper are posynomial GP problems, whose solutions can be obtained by solving a dual linear programing problem. The primary purpose of this paper is to investigate the quality of solutions found by, the application of a path-following algorithm, which is one of interior point methods. Two majorr approches to solve posynomial GP problems are investigated. One is dual GP as Generalized Lmear Programming (GLP) and the other is the traditional dual GP. The test results suggest that dual GP as GLP approach is advantageous over the posynomial one in the event that high a~curacy of the solution is required or critically important.